Cidade dos homens: etnografia de um salão masculino na periferia de São Paulo - Diniz, Gregório Zambon (2016)
Under the sign of the heterogeneity of the peripheries, treated as territories of a city and all its complexities this dissertation seeks, at first, to describe the work itself and its methodologies markedly by my entry into the field through an ethnographic methodology, starting a research in a men's parlor located on the eastern outskirts of São Paulo. It is from this parlor, as well as my travels around the city, strongly marked by the use of trains and subways, that my central points of observation occur. In this sense, I discuss the normalities and daily life at the parlor, taking the four hairdressers as central individuals of the research. Thus, in addition to tracing their life trajectories, I tried to apprehend the knowledge from the stories I heard, tracing and analyzing, thus, the reasons and motivations for which individuals circulate in the city, the relativity of money, values and valuations, as well how to clarify a city of men.